Incidence and management of acute otitis media in adults: a primary care-based cohort study. (28th January 2021) - Rijk, Merijn H; Hullegie, Saskia; Schilder, Anne G M; Kortekaas, Marlous F; Damoiseaux, Roger A M J; Verheij, Theo J M; Venekamp, Roderick P
Abstract: Background: Although primarily considered a childhood disease, acute otitis media (AOM) also occurs in adults. Data on the burden of this condition in adults are, however, scarce. Objective: To explore the primary care incidence and current management of AOM in adults. Methods: All patients aged 15 and older included in the routine health care database of the Julius General Practitioners' Network were followed from 2015 to 2018 (contributing to a total of 1 261 575 person-years). We extracted data on AOM episodes, AOM-related consultations, comorbidities, and antibiotic and analgesic prescriptions. Results: Five thousand three hundred and fifty-eight patients experienced one or more AOM episodes (total number of AOM episodes: 6667; mean 1.2 per patient). The overall AOM incidence was 5.3/1000 person-years and was fairly stable over the study period. Incidence was particularly high in atopic patients (7.3/1000 person-years) and declined with age (from 7.1 in patients 15–39 years of age to 2.7/1000 person-years in those aged 64 years and older). Oral antibiotics, predominantly amoxicillin, were prescribed in 46%, and topical antibiotics in 21% of all episodes. Conclusion: Over the past years, the incidence of AOM in adults in primary care has been stable. Oral antibiotic prescription rates resemble those in children with AOM, whereas a remarkably high topical antibiotic prescription rate was observed. Future prognostic research should inform on the need and feasibility of prospective studies into the best management strategy in this condition.